Recurrent Testicular Torsion of a Fixed Testis - Ibrahim Alnadhari; Ausama Abdulmuhsin; Omar Ali; Ahmad Shamsodini; Morshed Salah; Osama Abdeljaleel (Case Reports in Urology)
Recurrent testicular torsion after previous orchiopexy is rare and needs high index of suspension to avoid misdiagnosis and delayed management. This case showed that this diagnosis can occur even when the testis is still fixed to the scrotal wall. A 31-year-old male who had previous testicular fixation for testicular torsion with a single stitch to the lower pole before 6 years presented with recurrent testicular torsion and missed diagnosis. This case confirm that recurrent testicular torsion after previous fixation should be included in the differential diagnosis of acute scrotum and emphasis on the testicular fixation with nonabsorbable suture in at least two points to prevent recurrent torsion.